Android-Based Learning Application for Early Childhood Binayah Raudhatul Athfal Foundation - Putri, Ranti Eka; Yusman, Yanti; Pratama, Yuda Wira (International Conference on Sciences Development and Technology, 2022)
The binayah foundation is an educational foundation for early childhood that is characterized by Islam or raudhatul athfal. In organizing his education, Raudhatul Atfal instills the values of faith and piety to students in kindergarten (TK). As an educational foundation, Binayah Kindergarten requires innovation in presenting its teaching materials. This form of innovation is by utilizing technology that can create interesting and fun learning alternatives. This research designs and builds Android-based early childhood learning applications. The reason this application was built based on Android is because this application can provide knowledge in a different way that can be utilized by parents or kindergarten teachers by using smartphones android as a container for application installation. This application contains introductory material about hijaiyah, hadith, daily prayers, prayer readings, selected surahs, alphabets, numbers, and themes (professions, colors, animals, fruits and transportation).